Analysis of Mathematics Learning Difficulties in Grade VI Students at Miftahul Ulum Madrasah Ibtidaiyah In Solving Word Problems - Firdaus, Izzul Haq Candra; Fuady, Anies; Rohmah, Nur Nabilah Syahrur; Chasanah, Arini Nur (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Students who experience difficulties in learning mathematics often make mistakes in arithmetic and in the concepts used to solve story problems. The difficulties students often experience include solving story problems: they are unable to understand the problem's meaning and are confused about which arithmetic operation to use. The purpose of this study was to identify the difficulties students experience in learning mathematics and the factors that influence these difficulties in sixth grade at Miftahul Ulum Islamic Elementary School. This study used a qualitative descriptive method. The study subjects were 10 sixth-grade students and their homeroom teacher. The data collection procedures used were observation, interviews, tests, and documentation. The study found that 3 out of 10 sixth-grade students experience difficulties in learning mathematics when solving story problems. The difficulties in learning mathematics in solving story problems in the sixth grade included understanding concepts, calculating, and problem-solving. The factors causing difficulties in learning mathematics came from internal and external factors. Internal factors originating from students included IQ, student attitudes towards learning, and low student motivation to learn. Meanwhile, external factors originating from outside the students include a lack of variety in teaching methods, the use of learning media, and the environment.